Antimicrobial Barrier of an in vitro Oral Epithelial Model - Kimball, Janet R. (2006)
Oral epithelia function as a microbial barrier and are actively involved in recognizing and responding to bacteria. Our goal was to examine a tissue engineered model of buccal epithelium for its response to oral bacteria and proinflammatory cytokines and compare the tissue responses with those of a submerged monolayer cell culture. DESIGN: The tissue model was characterized for keratin and β-defensin expression. Altered expression of β-defensins was evaluated by RT-PCR after exposure of the apical surface to oral bacteria and after exposure to TNF-α in the medium. These were compared to the response in traditional submerged oral epithelial cell culture. RESULTS: The buccal model showed expression of differentiation specific keratin 13, hBD1 and hBD3 in the upper half of the tissue; hBD2 was not detected. hBD1 mRNA was constitutively expressed, while hBD2 mRNA increased 2-fold after exposure of the apical surface to three oral bacteria tested and hBD3 mRNA increased in response to the non-pathogenic bacteria tested. In contrast, hBD2 mRNA increased 3–600 fold in response to bacteria in submerged cell culture. HBD2 mRNA increased over 100 fold in response to TNF-α in the tissue model and 50 fold in submerged cell culture. Thus, the tissue model is capable of upregulating hBD2, however, the minimal response to bacteria suggests that the tissue has an effective antimicrobial barrier due to its morphology, differentiation, and defensin expression. CONCLUSIONS: The oral mucosal model is differentiated, expresses hBD1 and hBD3, and has an intact surface with a functional antimicrobial barrier.